Immunohistochemical distribution of secretagogin in the mouse brain - Téllez de Meneses, Pablo G.; Pérez-Revuelta, Laura; Canal-Alonso, Ángel; Hernández-Pérez, Carlos; Cocho, Teresa; Valero, Jorge; Weruaga, Eduardo; Díaz, David; Alonso, José R. (Frontiers in Neuroanatomy, 2023)
Calcium is essential for the correct functioning of the central nervous system, and calcium-binding proteins help to finely regulate its concentration. Whereas some calcium-binding proteins such as calmodulin are ubiquitous and are present in many cell types, others such as calbindin, calretinin, and parvalbumin are expressed in specific neuronal populations. Secretagogin belongs to this latter group and its distribution throughout the brain is only partially known. In the present work, the distribution of secretagogin-immunopositive cells was studied in the brain of healthy adult mice. Specific neural populations were observed in different zones and nuclei identified according to Paxinos mouse brain atlas. Labelled cells were found with a Golgi-like staining, allowing an excellent characterization of their dendritic and axonal arborizations. Many secretagogin-positive cells were observed along different encephalic regions, especially in the olfactory bulb, basal ganglia, and hypothalamus. Immunostained populations were very heterogenous in both size and distribution, as some nuclei presented labelling in their entire extension, but in others, only scattered cells were present. Secretagogin can provide a more complete vision of calcium-buffering mechanisms in the brain, and can also be a useful neuronal marker in different brain areas for specific populations.